Medication Safety in High-Risk Situations - (:unkn) unknown (World Health Organisation, 2019)
Each country participating in the third WHO Global Patient Safety Challenge: Medication Without Harm is urged to take early priority action to improve medication safety in high-risk situations and reduce harm by (5): Identifying its objectives by convening a group of technical experts, physicians, nurses, pharmacists, patients, regulators, and health system leaders to select and prioritize a small number of high-risk (high-alert) medications and high-risk situations for action that are applicable to their situation and achievable with the resources available; Developing a plan to achieve those objectives, including the processes, systems, patient involvement and education and training of health care professionals needed to deliver them; Developing a range of sustainable strategies of proven efficacy to address each of the priority areas in medication safety identified by the country, as medication errors are often caused by a combination of medication, provider and patient, and systems factors; Developing a strong safety culture within health care; Promoting and supporting the establishment of systems for reporting medication errors at national and institutional level.
Keywords: Inclusive Society; Medication safety; Patient safety